Characterisation of TCRab+, CD4-, CD8- Double-Negative T Cells in Murine Homeostasis and Cancer - Brennan, Martin (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2026)
Unconventional T cells bridge innate and adaptive immunity, combining features of both arms of the immune system. While iNKT, MAIT and yd T cells have been extensively studied as innate T cells in both homeostasis and disease, less is known about non-CD1d/MR1-restricted TCRab+ CD4+ CD8+ double-negative T cells (DNTs). Here, we characterize non-MAIT/iNKT/yd DNTs across murine tissues and investigate their potential innateness in comparison to other unconventional T cells. Combined single-cell TCR and RNA sequencing revealed a largely polyclonal and heterogeneous TCRab+ DNT population in the spleen and adipose tissue. Flow cytometric analysis shows DNTs account for 1-3% of T cells in secondary lymphoid organs but expand to 10-20% in non-lymphoid tissues such as adipose. We identify two dominant subtypes: type-1 DNTs (NK1.1+, T-bet+) and type-17 DNTs (CXCR6+, RORyt+), with broad tissue distribution. Phenotypically, DNTs share conserved innate T cell features, including expression of PLZF and Helios, a pre-activated effector-memory-like state, and rapid cytokine-driven effector function independent of TCR engagement. Subtype-specific enrichment of DNTs across various organs suggests specialised roles for DNTs in certain tissue environments, furthermore DNTs expand and 'fill the T cell niche' in knockout models which lack other T cell populations, supporting their tissue role. Additionally, we present evidence of distinct developmental requirements for both type-1 and type-17 DNTs in the thymus. DNT1 are MHC-I and -II independent, whereas DNT17 require a B2M-dependent restriction molecule that is Tap-independent, supporting distinct lineages for DNTs from other known T cell members. Finally, we demonstrate that type-1 DNTs, the most abundant subtype throughout murine tissues, and produce increased IFNy compared to other innate T cells in response to cytokine stimulation. DNT1s comprise the largest innate T cell population infiltrating multiple syngeneic tumour models. After ex-vivo expansion and adoptive transfer, DNT1s reduced tumour growth in the MC38 model, and induced an overall greater anti-tumour immune response encompassing many other immune cells, suggesting DNT1 cells facilitate increased immunogenicity. Together, our findings define DNTs as a thymically derived, innate-like T cell population with broad tissue distribution, distinct subtypes, and functional relevance in tumour immunity.
APPROVED